Association Between High Density Lipoprotein Level With Degree Of Stenosis In Coronary Artery Disease - Arrizki Azka Pratama; Saugi Abduh; Siti Thomas Zulaikhah (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2021)
Coronary Artery Disease (CAD) can be prevented by early detection and control of risk factors. This study aimed to determine the relationship of High Density Lipoprotein (HDL) levels with stenosis levels based on Significant Non-Significant angiography in CAD patients. Observational research method with cross-sectional design from secondary data at RSI Sultan Agung Semarang in January 2016 - October 2018, 363 respondents met the inclusion and exclusion criteria. Data were analyzed by Spearman test and logistic regression. In low HDL, significant stenosis was found to be 80.5% and non-significant 19.5%, significant HDL was found with significant stenosis 67.0% and non-significant 33.0%, whereas in high HDL, all (100%) with significant stenosis. The results with the Spearman test obtained p = 0.022. In the multivariate analysis of sex as the predominant variable (p=0,000; PR=4.743; 95%CI=1.496-4.109). age (p = 0.013; PR = 3.48; 95% CI = 1.24- 6.13), hypertension (p = 0.044; PR = 1.79; 95% CI = 1.10-3.17). There was a significant relationship between HDL levels and significant stenosis levels based on significant non-angiography in CAD patients and after being analyzed together with the disrupting variables as sex the most influential factors.